MENGUKUR HASIL BELAJAR EKONOMI MENGGUNAKAN MEDIA ASESMEN WORD SEARCH PUZZLE DI PLATFORM ANDROID - Siti Mujaiyanah (FKIP Unswagati, 2020)
ABSTRACTThe assessment media is used as a benchmark for students ability after pasticipating in learning, but if the assessment process is carried out using irrelevant media, he objectives of learning can not be achieved. This study aims to describe the feasinility, practicality, and effectiviness of the use of the Word Search Puzzle assessment media on the android platform. The research type is research and development (R&D) with ADDIE models from Dick and Carry which has 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The research trial design using the One Group Pretest Posttest Design, Validity product instrument were obtained from assessment expert, liguists, media expert, and student responses. The result showed that: (1) the development of the Word Search Puzzle assessment media is feasible, based on validation result with an average percentage of 75,93%; (2) Word Search Puzzle media is considered practical in learning because it is able to increase the interest of students, based on the students responses that get an average percentage of 88,92%; and (3) the Word Search Puzzle assessment media is affective to measure with the final result being 100% passed through classical completeness.Keywords: Word Search Puzzle, Assessment media, Learning outcomes